Molecular Modeling, Interacting Residues and other Structural Analyses for Human SOCS3, Gp130 and JAK Proteins: A Detailed Computational Approach for Proteins Involved in Feedback Inhibition - Banerjee, Arundhati; Dasgupta, Rakhi (Current Biotechnology, 2021)
Background: When STAT3 is activated only by the IL6 family of proteins, then gp130 (having a phosphopeptide motif) interacts with human SOCS3, which further binds to JAK and inhibits its protein kinase activity. Interaction of gp130 with SOCS3 targets only the IL-6 signaling cascade. The interaction occurs when SOCS3 binds to a particular motif on gp130 (centered upon pTyr759) after its phosphorylation. Previously, wet laboratory studies were done, but computational exploration for the participating residues remained unexplored. Methodology: The 3D structure of human SOCS3 protein was modeled, and its stereochemical parameters were satisfied. Crystallographic structures of gp130-phosphopeptide and JAK were studied. After protein docking, the complex underwent minimization and molecular dynamics simulation. Different stability parameters and binding patterns with residues were evaluated. Results and Discussion: The best-modeled structure of SOCS3 protein was selected and found that it had three helices and seven sheets interspersed with coils. Arg133, Tyr137 and Tyr98 from SOCS3 formed manifold binding patterns with gp130 (mainly with pTyr759 and Glu758). Lys62, Lys63 and Arg65 from SOCS3 were also found to interact with Val762 of gp130. Interactions with JAK were also studied. Residue 53, 62-65, 98, 133, 136 and 137 formed the predominant binding pockets in SOCS3. They can serve as important target sites as well. Altogether, it created electrostatically charged pockets to accommodate the partner proteins for each other. Gp130 phosphopeptide was observed to be tightly accommodated in the electrostatically positive zones on the SOCS3 surface. Net area for solvent accessibility was also found to get drastically reduced, implying high participation of residues. Earlier studies documented that the interaction of these three proteins occurs with affinity and have a satisfactory association with each other. Conclusion: Here in this study, the free energy of binding for the triple protein interaction through the ΔG values helped to infer that SOCS3 interacted spontaneously (in a thermodynamic sense). Many helical conformations formed coiled-coils providing high flexibility to interact spontaneously. Most of the interactions were through the responsible SH2 domain (46-127 residue length) of SOCS3. Residues 53, 62-64 and 98 formed coils while the residue number 137adopted sheet conformation from coils. Future Scope: This study shall instigate blocking the gp130-binding sites of SOCS3 through targeting of drugs, thereby preventing SOCS3-gp130 interaction. This would allow the JAK-STAT signaling cascade, which is paramount for several biological functions.
Keywords: Protein Interactions